Redeemable shares issued by hedge funds: a wrong turn in Cayman?. Issue 3 (2nd July 2016) - Harris, Daniel
Abstract : In the absence of a secondary market in the shares issued to their investors, hedge funds typically issue redeemable shares to enable investors to achieve liquidity by other means. For prospective investors, therefore, understanding the redemption terms attached to the shares to be issued is a critical part of the due diligence process. But even with such information, woe betide the prospective investor who invests without fully understanding where any claim for redemption proceeds ranks amongst other claimants in the event the fund becomes insolvent. In this article, the writer examines the recent decision of the Cayman Islands Court of Appeal in Herald Fund SPC v Primeo Fund (19 July 2016, unreported), which considered the question of whether certain claims for redemption proceeds rank pari passu with claims of ordinary unsecured creditors or are subordinated to them. It is argued that the decision represents a wrong turn in an area of Cayman Islands company law which is crucial to the hedge fund market.